Eosinophilic Granuloma of Mandible: A Report of Two Cases - Fonseca, Nigel; Saikrishna, D (Journal of Orofacial Research, 2014)
Eosinophilic granuloma of bone is a destructive osseous lesion characterized by large number of histiocytes. It is classified as one of the triad of nonlipid reticuloendothelial disorders, the Langerhans cell histiocytosis (LCH). The clinical manifestation varies from a localized lesion (eosinophilic granuloma) to a systemic disease. Typically, there is bone involvement and less frequently lesions might be found in other organs, particularly the lungs, liver, lymph nodes, skin and mucosa. It is curable by surgery, radiotherapy, chemotherapy, steroid injections or a combination of these techniques. We report two patients with eosinophilic granuloma exclusively limited to the mandible with review of features, the choice of method of treatment and outcome of the disease. Its diagnosis is based on clinical, radiographic and histopathological features. A complete excision of the lesions was performed in one case while the other was treated with low dose radiotherapy. Histopathological examination and IHC of the excised specimen confirmed diagnosis.